Medicaid Expansion at Title X Clinics: Client Volume, Payer Mix, and Contraceptive Method Type. Issue 6 (June 2019) - Boudreaux, Michel; Choi, Yoon Sun; Xie, Liyang; Marthey, Daniel
Abstract : Background: Title X supports access to family planning and preventive care services. Given its focus on low-income clients, Title X clinics may have been particularly affected by the Affordable Care Act's Medicaid expansion. Objectives: To examine the impact of the Affordable Care Act's Medicaid expansion on Title X client volumes, health insurance coverage, and contraceptive method mix. Research Design: A difference-in-differences design compared changes in the outcomes of interest before and after expansion, for expansion versus nonexpansion states. Subjects: Administrative data from Family Planning Annual Reports that describe Title X clients who sought services. Measures: Female client volume was measured using a participation ratio defined as the number of female clients per 100 women aged 15–44 with incomes <250% of the federal poverty line. We also examined the share of clients by insurance type and contraceptive method type. Results: We did not find evidence that expansion was related to changes in client volume. We did find a significant 9.9 percentage point increase in the share of clients with Medicaid and a significant 10.0 percentage point decrease in the share of clients without coverage. We found suggestive evidence that expansion was associated with increased use of long-acting reversible contraceptives, but those results were somewhat sensitive to model specification. Conclusions: Expansion was associated with meaningful increases in Medicaid coverage at Title X clinics and declines in uninsurance. Our results have important implications for the financial stability of Title X clinics in light of historical declines in Title X grant revenues. Abstract : Supplemental Digital Content is available in the text.